The interplay of IKK, NF‐κB and RIPK1 signaling in the regulation of cell death, tissue homeostasis and inflammation. Issue 1 (30th April 2017) - Kondylis, Vangelis; Kumari, Snehlata; Vlantis, Katerina; Pasparakis, Manolis
Summary: Regulated cell death pathways have important functions in host defense and tissue homeostasis. Studies in genetic mouse models provided evidence that cell death could cause inflammation in different tissues. Inhibition of RIPK3‐MLKL‐dependent necroptosis by FADD and caspase‐8 was identified as a key mechanism preventing inflammation in epithelial barriers. Moreover, the interplay between IKK/NF‐κB and RIPK1 signaling was recognized as a critical determinant of tissue homeostasis and inflammation. NEMO was shown to regulate RIPK1 kinase activity‐mediated apoptosis by NF‐κB‐dependent and –independent functions, which are critical for averting chronic tissue injury and inflammation in the intestine and the liver. In addition, RIPK1 was shown to exhibit kinase activity‐independent functions that are essential for preventing cell death, maintaining tissue architecture and inhibiting inflammation. In the intestine, RIPK1 acts as a scaffold to prevent epithelial cell apoptosis and preserve tissue integrity. In the skin, RIPK1 functions via its RHIM to counteract ZBP1/DAI‐dependent activation of RIPK3‐MLKL‐dependent necroptosis and inflammation. Collectively, these studies provided evidence that the regulation of cell death signaling plays an important role in the maintenance of tissue homeostasis, and suggested that cell death could be causally involved in the pathogenesis of inflammatory diseases.